An $L_1$ Minimization Problem by Generalized Rational Functions (Journal of Computational Mathematics, 1983)
Let $P,Q \subset L_1(X,Σ,μ)$ and $q(x)>0$ a. e. in $X$ for all $q\in Q$. Define $R=\{p/q:p\in P,q\in Q\}$. In this paper we discuss an $L_1$ minimization problem of a nonnegative function $E(z,x)$, i.e. we wish to find a minimum of the functional $φ(r)=\int _X qE(r,x)dμ$ form $r=p/q\in R$. For such a problem we have established the complete characterizations of its minimum and of uniqueness of its minimum, when both $P,Q$ are arbitrary convex subsets.